1999
DOI: 10.1177/000348949910801102
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Pouch Carcinoma: Real or Imaginary Risks?

Abstract: Pharyngeal pouch or Zenker's diverticulum presents to the otolaryngologist with symptoms of dysphagia. As supported by the published literature, the condition is more frequently seen in Northern Europe, especially the United Kingdom, than elsewhere in the world. The cause of the reported increased incidence in the United Kingdom is not known, but may be dietary. Surgical management is the treatment of choice and is directed at the cricopharyngeus muscle by either an external or an internal approach. There is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 27 publications
0
56
1
2
Order By: Relevance
“…The main predisposing factor is thought to be chronic inflammation of the pouch lining over many years, secondary to food retention. 23 The reported incidence varies widely but larger series have reported an incidence of 0. have been encountered by UK otolaryngologists with one surgeon reporting 5 cases. The diagnosis is often made at surgery, when cleaning of the pouch and careful examination with an oesophagoscope or Hopkins rod should be performed prior to any definitive surgical procedure..…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main predisposing factor is thought to be chronic inflammation of the pouch lining over many years, secondary to food retention. 23 The reported incidence varies widely but larger series have reported an incidence of 0. have been encountered by UK otolaryngologists with one surgeon reporting 5 cases. The diagnosis is often made at surgery, when cleaning of the pouch and careful examination with an oesophagoscope or Hopkins rod should be performed prior to any definitive surgical procedure..…”
Section: Discussionmentioning
confidence: 99%
“…However, cases of carcinoma in situ or small carcinomas may not be detected radiologically or by endoscopic examination. In a recent review by Bradley et al 23 two cases of carcinoma in situ were reported. Both of these had not been suspected clinically or found on endoscopy and the diagnosis was established by histopathological examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Squamous cell carcinoma in a ZD was first reported by Pitt in 1896 [64], with an estimated incidence of 0.4-1.5% [65][66][67][68]. There should be a high index of suspicion for development of a cancer within a ZD in the presence of alarm Review symptoms, which include neck pain, hemoptysis or hematemesis, an increase in the severity of dysphagia, regurgitation and malnutrition [65].…”
Section: Gastroesophageal Reflux Disease and Zdmentioning
confidence: 99%